Chronic pancreatitis and the composition of plasma phosphatidylcholine fatty acids - Zeman, Miroslav; Macášek, Jaroslav; Burda, Michal; Tvrzická, Eva; Vecka, Marek; Krechler, Tomáš; Staňková, Barbora; Hrabák, Petr; Žák, Aleš (Prostaglandins, leukotrienes, and essential fatty acids, 2016)
Chronic pancreatitis (CP) is an irreversible inflammatory disorder characterized by the destruction of both exocrine and endocrine tissue. There is growing evidence that dysregulation of fatty acid (FA) metabolism is connected with many diseases; however, there are few data concerning FA composition in CP. Therefore, we analyzed FA profiles in plasma phosphatidylcholines in 96 patients with CP and in 108 control subjects (CON). The patients with CP had, in comparison with CON, increased sum of monounsaturated FA (ΣMUFA) and decreased content of polyunsaturated FA (PUFA) in both n-6 and n-3 families. Moreover, CP patients had increased indexes for delta-9, delta-6 desaturases, and fall in activity of delta-5 desaturase. Increased ratio of 16:1n-7/18:2n-6 (marker of essential n-6 FA deficiency), was more prevalent among CP patients. These changes implicated decreased fat intake, including n-3 as well as n-6 PUFA, and intrinsic changes in FA metabolism due to the alteration of delta desaturase activities.
Keywords: metabolismus lipidů; Pancreatitis, Chronic; Humans; Fatty Acids, Unsaturated; kyseliny mastné mononenasycené; nenasycené mastné kyseliny; lidé středního věku; Lipid Metabolism; fosfatidylcholiny; chronická pankreatitida; Female; dospělí; lidé; Malnutrition; Adult; ženské pohlaví; Chronic pancreatitis; Male; Middle Aged; Phosphatidylcholines; mužské pohlaví; Fatty Acids, Monounsaturated; Diabetes mellitus; Fatty acid profile; Discriminant analysis